Migrating into Financial Markets : How Remittances Became a Development Tool - Savelsberg, Joachim J., 1951- (Book collections on Project MUSE., 2015)
How do interventions by the UN Security Council and the International Criminal Court influence representations of mass violence? What images arise instead from the humanitarianism and diplomacy fields? How are these competing perspectives communicated to the public via mass media? Zooming in on the case of Darfur, Joachim J. Savelsberg analyzes more than three thousand news reports and opinion pieces and interviews leading newspaper correspondents, NGO experts, and foreign ministry officials from eight countries to show the dramatic differences in the framing of mass violence around the world and across social fields. Representing Mass Violencecontributes to our understanding of how the world acknowledges and responds to violence in the Global South.